Evaluation of microneedle arrays as potential delivery systems for bacterial extracellular vesicles - Sousa, Miriam Domingos de (2023)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, 2023, Universidade de Lisboa, Faculdade de Farmácia.